Quality of life after total laryngectomy: evaluating the effect of socioeconomic status. Issue 2 (18th February 2019) - Scott, A J; McGuire, J K; Manning, K; Leach, L; Fagan, J J
Abstract: Objective: Total laryngectomy is considered the primary treatment modality for advanced laryngeal carcinoma. This study assessed the quality of life in patients after total laryngectomy, and ascertained whether quality of life is affected by socioeconomic status. Method: Forty-seven patients (20 state- and 27 private-sector) who underwent total laryngectomy between 1998 and 2014 responded to the University of Washington Quality of Life Questionnaire, the Voice-Related Quality of Life Questionnaire and the Brief Illness Perception Questionnaire. Results: Significant differences were found in socioeconomic status between state- and private-sector patients ( p < 0.001). There was no significant difference in overall quality of life between groups ( p = 0.210). State-sector patients scored significantly higher Voice-Related Quality of Life Questionnaire scores ( p = 0.043). Perception of illness did not differ significantly between groups. Conclusion: Overall quality of life after total laryngectomy appears to be similar in patients from different socioeconomic backgrounds. However, patients from lower socioeconomic circumstances have better voice-related quality of life. The results illustrate the importance of including socioeconomic status when reporting voice outcomes in total laryngectomy patients.